The Impact of Oil Shocks on Business Cycles and Structural Inflation in Iran: An SVAR Approach - Mirabizadeh, Masoumeh (Business, Marketing, and Finance Open, 2026)
This study aims to examine the dynamic effects of oil price shocks on Iran’s business cycles and structural inflation by identifying their transmission mechanisms through output, inflation, and exchange rate channels. A quarterly time-series dataset covering 1990Q1–2023Q4 was employed, encompassing real GDP, Consumer Price Index (CPI), real oil price, exchange rate, and money supply. After testing for stationarity and cointegration, a Structural Vector Autoregressive (SVAR) model with two lags was estimated to capture both short-run and long-run dynamics. Identification was achieved through theoretically grounded short-run restrictions distinguishing exogenous oil shocks from domestic policy innovations. Impulse Response Functions (IRFs) and Forecast Error Variance Decomposition (FEVD) were computed to assess the magnitude, direction, and persistence of macroeconomic responses to a one standard deviation oil shock. Inflation was further decomposed into structural (trend) and cyclical components using the Hodrick–Prescott filter to distinguish between transitory and persistent effects. Results indicate that a positive oil price shock initially raises real GDP for two quarters through fiscal expansion but subsequently contracts output after the fourth quarter due to inflationary pressures and cost escalation. CPI responds immediately and persistently, peaking at around 0.9% above baseline by the third quarter, confirming strong price pass-through effects. The exchange rate depreciates after two quarters, amplifying inflation via import prices. FEVD results reveal that oil shocks explain approximately 31% of output variance and 57% of inflation variance at medium horizons. Structural decomposition shows that oil shocks primarily drive short-run cyclical inflation, while long-run inflation persistence stems from fiscal and monetary rigidity. Oil price shocks exert asymmetric and time-dependent effects on Iran’s economy—stimulating short-term output but intensifying long-term structural inflation through fiscal expansion, monetary accommodation, and exchange rate depreciation. Effective macroeconomic stabilization requires counter-cyclical fiscal policy, monetary discipline, and institutional reforms to reduce vulnerability to external oil fluctuations.